Chalcogenide Ovonic Threshold Switching Selector - Zhao, Zihao; Clima, Sergiu; Garbin, Daniele; Degraeve, Robin; Pourtois, Geoffrey; Song, Zhitang; Zhu, Min (Nano-Micro Letters, 2024)
Today’s explosion of data urgently requires memory technologies capable of storing large volumes of data in shorter time frames, a feat unattainable with Flash or DRAM. Intel Optane, commonly referred to as three-dimensional phase change memory, stands out as one of the most promising candidates. The Optane with cross-point architecture is constructed through layering a storage element and a selector known as the ovonic threshold switch (OTS). The OTS device, which employs chalcogenide film, has thereby gathered increased attention in recent years. In this paper, we begin by providing a brief introduction to the discovery process of the OTS phenomenon. Subsequently, we summarize the key electrical parameters of OTS devices and delve into recent explorations of OTS materials, which are categorized as Se-based, Te-based, and S-based material systems. Furthermore, we discuss various models for the OTS switching mechanism, including field-induced nucleation model, as well as several carrier injection models. Additionally, we review the progress and innovations in OTS mechanism research. Finally, we highlight the successful application of OTS devices in three-dimensional high-density memory and offer insights into their promising performance and extensive prospects in emerging applications, such as self-selecting memory and neuromorphic computing. Highlights: 1 The development history and key milestones of ovonic threshold switch (OTS) materials were comprehensively summarized. Combined with the latest advancements of OTS research, the mainstream OTS material systems were systematically introduced. 2 A thorough overview of the prevailing viewpoints regarding the OTS switching mechanisms was presented. 3 Recent progress in OTS devices for applications in 3D memory, self-selecting memory, and neuromorphic computing was summarized.